Mengenang sepuluh tahun bencana industri lumpur Lapindo dan tindakan kolektif para korban - Sukamto Sukamto (Universitas Negeri Malang, 2016)
This article aims to commemorate an extraordinary event called Industrial Disaster. This disaster occurred a long time, where the source bursts can not be stopped until now. Casualties are quite a lot, there is even a village wiped off the map, because the entire surface of the devastated hit by the mud. Settlement of sosial problems has just ended after the Government granted bail money as payment of